2001
DOI: 10.1021/jp012012s
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical, Electrochemical, and Electrogenerated Chemiluminescent Properties of 9,10-Dimethyl-7,12-diphenylbenzo[k]fluoranthene and 9,10-Dimethylsulfone-7,12-diphenylbenzo[k]fluoranthene

Abstract: A newly synthesized light emitting compound 9,10-dimethylsulfone-7,12-diphenylbenzo[k]fluoranthene (DSDPBF) and its synthetic intermediate 9, 10-dimethyl-7,12-diphenylbenzo[k]fluoranthene (DMDPBF) were studied to evaluate how the addition of weak electron donating methyl groups and the subsequent addition of an electron withdrawing sulfone group affect the photophysical and electrochemical properties as well as the rate of radical cation coupling of the parent compound, 7,12-diphenylbenzo[k]fluoranthene (DPBF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…Brighter ECL than their unsubstituted counterparts was also observed for 5,11-diphenyltetracene or 9,10-dimethyl-7,12-diphenylbenzo[k]fluoranthene. 125 Alkyl or aryl functionalization tends in formation of more stable radical cations that results brighter ECL emission. Due to sterical effects the functionalization may also results in weaker intermolecular interactions between R À and R þ that marginalizes the formation of weakly emissive excimer 1Ã R 2 and 3Ã R 2 states with increasing efficiency of the excited 1Ã R populations.…”
Section: Organic Ecl Systems Electrochemical Excitation In Organic Eclmentioning
confidence: 99%
“…Brighter ECL than their unsubstituted counterparts was also observed for 5,11-diphenyltetracene or 9,10-dimethyl-7,12-diphenylbenzo[k]fluoranthene. 125 Alkyl or aryl functionalization tends in formation of more stable radical cations that results brighter ECL emission. Due to sterical effects the functionalization may also results in weaker intermolecular interactions between R À and R þ that marginalizes the formation of weakly emissive excimer 1Ã R 2 and 3Ã R 2 states with increasing efficiency of the excited 1Ã R populations.…”
Section: Organic Ecl Systems Electrochemical Excitation In Organic Eclmentioning
confidence: 99%
“…20 The bluish fluoranthene derivatives have a large spectrum shift between the solid and solution state photoluminescence (PL), possibly because the strongest emission peak is not from the 0-0 transition state, or the effect of strong reabsorption weakens the deep blue emission. In the fluoranthene families, benzo[k]fluoranthene has outstanding deep blue emission characteristics 23,24 + 2] cycloadditions, in which the different substituents can be easily attached to the core by varying the reactants. 23 This feature enables the screening and tuning of the photo-physical properties of these molecules.…”
Section: Introductionmentioning
confidence: 99%
“…1 In this regard, fluoranthene-fused sulfones such as 1 act as a light-emitting compound. 2 Moreover, fluoranthene derivatives (Figure 1), such as 2 and 3, 3a and 4 and 5, 3b,c exhibit interesting photophysical and electrochemical properties, and compounds such as 6 act as fluorescent chemosensors for the detection of explosives such as 2,4,6-trinitrotoluene and picric acid. 3d In view of the interesting photophysical and electrochemical properties of various fluoranthene-fused derivatives, strategies for their syntheses are of great interest.…”
mentioning
confidence: 99%
“…3d In view of the interesting photophysical and electrochemical properties of various fluoranthene-fused derivatives, strategies for their syntheses are of great interest. [2][3][4] To this end, Fabrizio et al reported the synthesis of fluoranthene-fused sulfone derivatives such as 9,10-dimethylsulfone-7,12-diphenylbenzo[k]fluoranthene 1 (DSDPBF) 2 employing the Diels-Alder reaction. On the other hand, Pei and co-workers reported the synthesis of fluoranthene-fused imide derivatives 3b,c using the Diels-Alder reaction and decarbonylation as key steps.…”
mentioning
confidence: 99%
See 1 more Smart Citation